2020
DOI: 10.2967/jnmt.119.239285
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patient Experience in a Nuclear Medicine Department: Comparison Between Bone Scintigraphy and 18F-FDG PET/CT

Abstract: Our objective was to assess the anxiety level in cancer patients undergoing nuclear medicine exams and to identify how professionals can improve patient experience. Methods: In total, 94 patients undergoing 99m Tc-hydroxymethylene diphosphonate ( 99m Tc-HDP) bone scintigraphy (BS) or 18 F-FDG PET/CT completed 2 scan-experience questionnaires and the Spielberger State Anxiety Inventory (STAI-S) before the scan and after image acquisition. Results: Before the exam, the mean anxiety levels were higher for the 99m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(83 reference statements)
0
2
0
Order By: Relevance
“… 15 18 20 23–26 29 30 32 33 35 37 38 44–46 49 52–54 56 58 60 61 There were six exceptions, which reported maximal mean severity scores of: 5.5 out of 10 (Likert scale) 17 ; 6.4 out of 10 (Likert scale) 50 ; 4.1 out of 7 (Likert scale), 40 33 out of 60 (STAI state anxiety subscale), 51 8.1 out of 14 (Health Questionnaire) 58 ; and 51.75 out of 80 (STAI). 59 Four of these scores occurred in studies where scans were performed for reasons other than screening, 17 50 51 59 one allowed scans for diagnosis or screening 40 and one allowed scans for screening only. 58 …”
Section: Resultsmentioning
confidence: 99%
“… 15 18 20 23–26 29 30 32 33 35 37 38 44–46 49 52–54 56 58 60 61 There were six exceptions, which reported maximal mean severity scores of: 5.5 out of 10 (Likert scale) 17 ; 6.4 out of 10 (Likert scale) 50 ; 4.1 out of 7 (Likert scale), 40 33 out of 60 (STAI state anxiety subscale), 51 8.1 out of 14 (Health Questionnaire) 58 ; and 51.75 out of 80 (STAI). 59 Four of these scores occurred in studies where scans were performed for reasons other than screening, 17 50 51 59 one allowed scans for diagnosis or screening 40 and one allowed scans for screening only. 58 …”
Section: Resultsmentioning
confidence: 99%
“…It is recognized that high-technology imaging presents a potential source of patient anxiety, which can limit adequate scan completion (4)(5)(6)(7)(8)(9). We sought to assess the claustrophobia rate in 2 ways.…”
Section: Discussionmentioning
confidence: 99%
“…A review of current literature regarding the patient experience of medical imaging revealed similar studies of patient experience and tolerability of MRI and nuclear imaging (4)(5)(6)(7)(8). Informed by one of these studies (4), a cross-sectional patient experience questionnaire was drafted, which contained 4 measures of scan experience (comfort, scan time, scan noise, and claustrophobia).…”
Section: Questionnaire Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Th ey found that the most prominent factor causing anxiety in both bone scintigraphy and PET/CT scan was the imaging time. 26 In a recent study using the STAI questionnaire 25 , Sun et al found that patients with a confi rmed diagnosis of a malignancy had higher anxiety levels than asymptomatic healthy people undergoing cancer screening. In their study, the procedure was introduced to the patients before the PET/CT scan by a video recording, and the number of patients with anxiety was found to be decreased in the patient group compared to the control group, with lower STAI-related scores.…”
Section: Discussionmentioning
confidence: 99%